Modeling decisions for artificial intelligence : 14th International Conference, MDAI 2017, Kitakyushu, Japan, October 18-20, 2017, Proceedings /: 14th International Conference, MDAI 2017, Kitakyushu, Japan, October 18-20, 2017, Proceedings. (2017) - Unknown
No abstract available